2014
DOI: 10.1242/jeb.101139
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive changes in echolocation sounds byPipistrellus abramusin response to artificial jamming sounds

Abstract: The echolocation behavior of Pipistrellus abramus during exposure to artificial jamming sounds during flight was investigated. Echolocation pulses emitted by the bats were recorded using a telemetry microphone mounted on the bats' backs, and their adaptation based on acoustic characteristics of emitted pulses was assessed in terms of jamming-avoidance responses (JARs). In experiment 1, frequency-modulated jamming sounds (3 ms duration) mimicking echolocation pulses of P. abramus were prepared. All bats showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 27 publications
6
27
0
Order By: Relevance
“…Echoing has been proposed to serve a jamming avoidance function during active electrolocation (8,9), a notion contested by the observation that object discrimination in Gnathonemus petersii was not impaired during jamming (33). However, jamming avoidance also occurs in other active sensory systems such as active electrolocation in gymnotiform weakly electric fish (34,35) and echolocation in bats (36). The necessity for a jamming avoidance strategy is apparent in gymnotiforms because they lack a reafferent neuronal pathway, which enables mormyrids to distinguish between self-and nonself-generated EODs (37).…”
Section: Discussionmentioning
confidence: 99%
“…Echoing has been proposed to serve a jamming avoidance function during active electrolocation (8,9), a notion contested by the observation that object discrimination in Gnathonemus petersii was not impaired during jamming (33). However, jamming avoidance also occurs in other active sensory systems such as active electrolocation in gymnotiform weakly electric fish (34,35) and echolocation in bats (36). The necessity for a jamming avoidance strategy is apparent in gymnotiforms because they lack a reafferent neuronal pathway, which enables mormyrids to distinguish between self-and nonself-generated EODs (37).…”
Section: Discussionmentioning
confidence: 99%
“…Stationary T. brasiliensis reduce the number of pulses in the presence of interfering sounds and conspecifics 36, 37 . Similarly, flying P. abramus 22 , T. brasiliensis 38 and E. fuscus 39 bats regulate vocal timing in response to jamming sounds or the sounds of conspecifics in the group. Moreover, the directionality and directivity of the ears and pulses serve as spatial filters, allowing bats to focus on a point in three-dimensional space and ignore sounds that come from off-axis angles.…”
Section: Discussionmentioning
confidence: 99%
“…The conventional recording methodology with fixed microphones can be used to identify individuals, especially over short distances, but one must take into account that the recorded sounds will be distorted to some extent (e.g., by the Doppler effect and atmospheric attenuation). Recently, we have used miniature on-board microphones, which measure the sounds of bats without distortion, to investigate echolocation pulses emitted by flying bats under acoustic jamming conditions; we have shown that frequency-modulating bats shift their terminal frequencies during flight depending on the frequency of presented pulse mimics 22, 23 . This technique can directly capture how each bat flying in a group changes its pulse characteristics to avoid jamming, and the present study is the first that we are aware of to demonstrate experimentally the relationship between the terminal frequencies of pairs of individuals during group flight.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, by analyzing the distribution of retrogradely labeled cells inside the IC, we identified cell types that make long‐range intrinsic connection inside the IC. Although this species have been used frequently on biosonar studies (Fujioka et al., 2014; Sumiya, Fujioka, Motoi, Kondo, & Hiryu, 2017; Takahashi et al., 2014; Yamada, Hiryu, & Watanabe, 2016), the information about the organization of auditory pathways of this species has not been reported except for a single unit recording study from the IC (Goto, Hiryu, & Riquimaroux, 2010). Therefore, our study will give new neuroethological insights on biosonar.…”
Section: Introductionmentioning
confidence: 99%